STATISTICAL PROCESS CONTROL MODEL IN THE DESIGN AND THE DEVELOPMENT OF FABRICS - B. Gjorgjevska; S. Kjortosheva; V. Chepujnoska (Journal of Engineering & Processing Management, 2010)
In this paper the aim was to create a basic model for total quality management in the organization of the textile production, with an emphasis on Statistical Process Control (SPC) in the design and development process that will completely satisfy the requirements, the needs and the desires of the buyers and all the participants in the business relations. The paper deals with a methodology of the process of fabric’s design and development, consisted of two macro stages: 1) development and 2) fabric’s production. The monitoring, the analysis and the verification of the process were done using statistical methods, techniques and tools, with which in the most explicit manner data processing, analysis and presentation are done. This is aimed at continuous process improvement. According to this, a few methods were presented: FMEA method, Pareto and Cause and Effect analysis and X - R control chart.
Keywords: FMEA; Pareto analysis; Cause and Effect analysis; X-R control chart; design; development; fabrics; project; process